Effect of Supportive Education on Knowledge and Practice of Kangaroo-Mother-Care in Pre-term and Low-Birth-Weight Babies Management in Selected Communities in Enugu State, Southeastern Nigeria (African Journal of Biomedical Research, 2024)
This study assessed the effect of supportive education on the knowledge and practice of kangaroo-mother-care (KMC) in the management of pre-mature and low-birth-weight babies in selected communities in Enugu State. A quasi-experimental pretest-posttest, non-randomized design was adopted. A sample size of 332 postnatal mothers from the two community health centers under study was determined using power analysis. A structured questionnaire was used as an instrument for data collection. Data were descriptively analyzed with SPSS version 22, while inferential statistical analysis was performed using the chi-square test, independent t test, and one-way analysis of variance. Results with a p < 0.05 were considered statistically significant. Results of major findings showed that mothers' knowledge of KMC improved after the intervention, from an average score of 34.8% to 85.6% and 31.9% to 69.2%, with mean and standard deviations of 6.8±2.6 and 5.6±2.9 in the experimental and control groups, respectively. The practice of KMC also improved after the intervention, from 30% to 76.6% and 36.4% to 73.5%, with mean and standard deviations of 7.7±1.2 and 6.6±1.5 in the experimental and control groups, respectively. There was a significant difference in mothers knowledge of KMC between the experimental and control groups before the intervention (t =2.6 and p = 0.010) and after the supportive intervention (t = 3.7 and p = 0.000). There was no significant difference in the influence of socio-demographic characteristics of mothers and the practice of KMC after intervention in both groups: educational status (F = 0.3 and p = 0.801), marital age (F = 0.3 and p = 0.889), and parity (F = 0.1 and p = 0.965). In conclusion, participants with supportive education interventions (experimental group) performed better than those with normal health education (control group).